Analisis Pengembangan Model Pembelajaran terhadap Kemampuan Berfikir Kreatif Siswa Kelas 3 SD Secara Daring/Online - Magdalena, Ina; Nabilah, Nabilah; Lestari, Linda (YASIN, 2021)
The purpose of this study was to describe the development of learning models on the creative thinking skills of elementary school students at SDN Kalideres 06 Pagi, and to produce learning and creative models of students in elementary school life. This research is an activity that must be understood by a teacher how to develop students' creative thinking in the learning model created. And with this research, we can find out the thinking patterns of students and we can also understand how a teacher teaches the right model or method to students so they can think creatively. This descriptive research was conducted at the elementary school level to find out how the learning outcomes of students, especially in grade 3. 3 SDN Kalideres 06 am. The result is that at SDN Kalideres 06 in the morning there are still many students who have not been able to think creatively and have not been able to understand the methods taught by the teacher